Penerapan Media Komik Digital untuk Meningkatkan Hasil Belajar IPA Peserta Didik kelas VIII SMP Negeri 2 Bajeng - Rezky Amaliyah Rifai; Salma Samputri; Nurhayani H. Muhiddin (Celebes Science Education, 2025)
This research aims to determine: 1) the level of learning outcomes of class VIII students at SMP Negeri 2 Bajeng before being taught using digital comic media on light and optics, 2) the level of learning outcomes for class VIII students at SMP Negeri 2 Bajeng after being taught using digital comic media on light and optical materials. 3) Improving the learning outcomes of class VIII students at SMP Negeri 2 Bajeng by applying digital comic media to light and optical instruments. 4) after there was no significant increase in the learning outcomes of class VIII students at SMP Negeri 2 Bajeng implementing digital comic media. The type of research is Pre-Experimental research with a research design using One Group Pre-test- Post-test. The samples were selected by random sampling, with 2 classes, namely classes VIII A and VIII B, totaling 28 samples. Based on the results of the research it was concluded: 1) The level of learning outcomes for class VIII students at SMP Negeri 2 Bajeng before implementing digital comic media was in the low category with an average score of 8.43. 2) The level of learning outcomes for class VIII students at SMP Negeri 2 Bajeng after implementing digital comic media is in the sufficient category with a score of 16.04. 3) The increase in student learning outcomes is in the medium category with a score of 0.46. 4) Digital comic media can improve learning outcomes, this is proven by testing the hypothesis using a paired sample test to obtain Sig (2-tailed) = 0.000 which shows that H0 is rejected and H1 is accepted.